The third space of sovereignty : the postcolonial politics of U.S.-indigenous relations - Bruyneel, Kevin (Indigenous Americas., 2007)
The Third Space of Sovereignty offers fresh insights on such topics as the end of treaty-making in 1871, U.S. citizenship in the 1920s, native politics during the civil rights era, and the current issues surrounding casinos. Kevin Bruyneel shows how native political actors have effectively contested the limits that the United States has imposed on their ability to develop economically and politically on their own terms.